The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/iop.0000000000001063
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Induced Crosslinking of Tarsal Collagen as a Treatment for Eyelid Laxity: Assessing Potentiality in Animal Tissue

Abstract: These findings indicate that irradiation of tarsal collagen leading to tissue stiffening could be a safe procedure for treating lax eyelid conditions in human patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…They found no significant effects of low levels of irradiance (3–6 mW/cm 2 ) on stiffness. However, at much higher levels of irradiance (30 and 45 mW/cm 2 ), cross-linked samples significantly stiffened 7. The higher levels of irradiance used by Smith and colleagues7 cannot be used safely in humans.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…They found no significant effects of low levels of irradiance (3–6 mW/cm 2 ) on stiffness. However, at much higher levels of irradiance (30 and 45 mW/cm 2 ), cross-linked samples significantly stiffened 7. The higher levels of irradiance used by Smith and colleagues7 cannot be used safely in humans.…”
Section: Discussionmentioning
confidence: 95%
“…However, at much higher levels of irradiance (30 and 45 mW/cm 2 ), cross-linked samples significantly stiffened 7. The higher levels of irradiance used by Smith and colleagues7 cannot be used safely in humans. However, in the current human study, lower irradiance (6 mW/cm 2 ) significantly stiffened tarsal plates.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Riboflavin, a photosensitizer applied directly to the corneal stromal collagen, is exposed to UVA (ultraviolet A) radiation, inducing bond formation between collagen fibers (primarily type I and III) and increasing corneal stiffness [19, 20]. In addition, a recent study demonstrated significant stiffening of sheep tarsal plate tissue following collagen crosslinking [21].…”
Section: Introductionmentioning
confidence: 99%